2016
DOI: 10.1038/srep33823
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase-2 induced β1-integrin expression in NSCLC and promoted cell invasion via the EP1/MAPK/E2F-1/FoxC2 signal pathway

Abstract: Cyclooxygenase-2 (COX-2) has been implicated in cell invasion in non-small-cell lung cancer (NSCLC). However, the mechanism is unclear. The present study investigated the effect of COX-2 on β1-integrin expression and cell invasion in NSCLC. COX-2 and β1-integrin were co-expressed in NSCLC tissues. COX-2 overexpression or Prostaglandin E2 (PGE2) treatment increased β1-integrin expression in NSCLC cell lines. β1-integrin silencing suppressed COX-2-mediated tumour growth and cancer cell invasion in vivo and in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 34 publications
3
31
0
Order By: Relevance
“…These results reveal that the PGE 2 /ANGPTL4 axis regulates tumor cell migration and invasion through the promotion of tumor‐endothelial cell interactions. In addition, previous reports indicated that COX‐2 enhances β1 integrin expression to promote non‐small‐cell lung cancer cell invasion 48 . In our previous studies, we have shown that EGF‐induced ANGPTL4 activates the integrin pathway to promote HNSCC metastasis 5 .…”
Section: Discussionmentioning
confidence: 82%
“…These results reveal that the PGE 2 /ANGPTL4 axis regulates tumor cell migration and invasion through the promotion of tumor‐endothelial cell interactions. In addition, previous reports indicated that COX‐2 enhances β1 integrin expression to promote non‐small‐cell lung cancer cell invasion 48 . In our previous studies, we have shown that EGF‐induced ANGPTL4 activates the integrin pathway to promote HNSCC metastasis 5 .…”
Section: Discussionmentioning
confidence: 82%
“…This seminal study and others to follow identified FOXC2 as a key regulator of EMT, a pathway key to tumor cell metastasis that is driven by FOXC2's direct repression of p120ctn and direct induction of Zeb1 (23,24), both of which lead to down-regulation of E-cadherin, a major hallmark of EMT. In another study, FOXC2 has been shown to promote non-small cell lung cancer cell migration and invasion through up-regulation of Itgb1 gene expression (25). It has also been shown to drive osteosarcoma metastasis to lung tissue via a CXCR4-dependent mechanism (26).…”
Section: Discussionmentioning
confidence: 96%
“…It has been reported that COX2 is upregulated in different cancers and its elevation results in a poor prognosis such as axillary node and bone metastases, and chemotherapy resistance [ 22 26 ]. Inhibition of COX2 can act in a concerted way with improved therapeutic potential in invasive breast cancer, non small cell lung cancer, bladder cancer and cervical cancer [ 18 , 27 29 ].…”
Section: Introductionmentioning
confidence: 99%